Identification of an ICP27-Responsive Element in the Coding Region of a Herpes Simplex Virus Type 1 Late Gene - Sedlackova, Lenka (American Society for Microbiology (ASM), 2010)
During productive herpes simplex virus type 1 (HSV-1) infection, a subset of viral delayed-early (DE) and late (L) genes require the immediate-early (IE) protein ICP27 for their expression. However, the cis-acting regulatory sequences in DE and L genes that mediate their specific induction by ICP27 are unknown. One viral L gene that is highly dependent on ICP27 is that encoding glycoprotein C (gC). We previously demonstrated that this gene is posttranscriptionally transactivated by ICP27 in a plasmid cotransfection assay. Based on our past results, we hypothesized that the gC gene possesses a cis-acting inhibitory sequence and that ICP27 overcomes the effects of this sequence to enable efficient gC expression. To test this model, we systematically deleted sequences from the body of the gC gene and tested the resulting constructs for expression. In so doing, we identified a 258-bp “silencing element” (SE) in the 5′ portion of the gC coding region. When present, the SE inhibits gC mRNA accumulation from a transiently transfected gC gene, unless ICP27 is present. Moreover, the SE can be transferred to another HSV-1 gene, where it inhibits mRNA accumulation in the absence of ICP27 and confers high-level expression in the presence of ICP27. Thus, for the first time, an ICP27-responsive sequence has been identified in a physiologically relevant ICP27 target gene. To see if the SE functions during viral infection, we engineered HSV-1 recombinants that lack the SE, either in a wild-type (WT) or ICP27-null genetic background. In an ICP27-null background, deletion of the SE led to ICP27-independent expression of the gC gene, demonstrating that the SE functions during viral infection. Surprisingly, the ICP27-independent gC expression seen with the mutant occurred even in the absence of viral DNA synthesis, indicating that the SE helps to regulate the tight DNA replication-dependent expression of gC.